The complete chloroplast genome sequences of Larix kaempferi and Larix olgensis var. koreana (Pinaceae) - Sang-Chul Kim; Jei-Wan Lee; Min-Woo Lee; Seung-Hoon Baek; Kyung-Nak Hong (Mitochondrial DNA. Part B. Resources, 2018)
The complete chloroplast (cp) genome sequence of Larix kaempferi and L. olgensis var. koreana were determined by Ion torrent Platform sequencing in this study. The L. kaempferi cp genome was 122,158bp consists of two inverted repeat (IR) regions of 436bp each, a large single-copy (LSC) region of 65,394bp, and a small single-copy (SSC) region of 55,892bp. The chloroplast genome sequence of L. olgensis var. koreana was 122,573bp in length, consisting of two IRs (436bp), one LSC (65,597bp), and one SSC (56,104bp), and is longer than that of L. kaempferi. The genome contained 110 genes, including 71 protein-coding genes, 35 tRNA genes, and 4 ribosomal RNA genes. The 13 genes contain introns, including 12 genes with a single intron each and ycf3 gene with two introns. And, the rps12 gene is a trans-spliced gene. The phylogenetic analysis revealed that all sampled species in Pinaceae formed a monophyletic clade with high bootstrap value. The genus Larix is closely related to Pseudotsuga.